2015
DOI: 10.1021/acs.orglett.5b00276
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Selective Hydrogenation of 3-Hydroxypyridinium Salts: A Facile Synthesis of Piperidin-3-ones

Abstract: The selective hydrogenation of 3-hydroxypyridinium salts has been achieved using a homogeneous iridium catalyst, providing a direct access to 2- and 4-substituted piperidin-3-one derivatives with high yields, which are important organic synthetic intermediates and the prevalent structural motifs in pharmaceutical agents. Mild reaction conditions, high chemoselectivity, and easy scalability make this reaction highly practical for the synthesis of piperidin-3-ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…13 C‐NMR (DMSO‐d6, 125.76 MHz) δ=151.48, 144.38, 140.19, 137.99, 128.79, 127.68, 123.49, 123.31 ppm. Results were in agreement with literature [38] …”
Section: Methodssupporting
confidence: 92%
“…13 C‐NMR (DMSO‐d6, 125.76 MHz) δ=151.48, 144.38, 140.19, 137.99, 128.79, 127.68, 123.49, 123.31 ppm. Results were in agreement with literature [38] …”
Section: Methodssupporting
confidence: 92%
“…Recently, Zhou et al reported an iridium-catalyzed hydrogenation of 3-hydroxypyridinium salts, but this reaction is restricted to the formation of 6- H -piperidin-3-ones (eq 2 in Figure ). Moreover, to the best of our knowledge, the synthesis of piperidin-3-ones bearing quaternary carbons are still unexplored. In this context, the search for a step-economical and efficient system to generate structural diversity of piperidin-3-ones is of great value.…”
mentioning
confidence: 99%
“…R f = 0.5 (5:1 chloroform/diethyl ether) [UV]; mp = 228 °C; IR (NaCl, cm −1 ) ν; 2417,1574,1510,1460,1358,1280,1221,1181,1156,1118,1078,835,797,761; 1 H NMR (600 MHz, (CD 3 ) 2 SO) δ 10.21 (s, 1H), 8.14 (dd, J = 4.5, J = 1.4 Hz, 1H), 8.08 (dd, J = 9.1 Hz, J HF = 5.8 Hz, 2H), 7.33 (dd, J = 8.2 Hz, J = 1.5 Hz, 1H), 7.24 (t, J HF = 9.0 Hz, J = 9.0 Hz, 2H), 7.20 (dd, J = 8.2, J = 4.5 Hz, 1H); 13 C NMR (151 MHz, (CD 3 ) 2 SO) δ 161.7 (d, J CF = 244.9 Hz), 151.3, 143.1, 140.1, 134.3 (d, J CF = 3.0 Hz), 130.7 (d, J CF = 8.2 Hz), 123.6, 123.5, 114.4 13 C NMR data are in agreement with those previously reported. 29 2-(4-Bromophenyl)pyridin-3-ol (3c). Compound 3c was prepared according to GP1 using 4-bromophenyldiazonium chloride (2c).…”
mentioning
confidence: 99%
“…The melting point obtained is in agreement with the value previously reported. 29 N-(4-(3-Hydroxypyridin-2-yl)phenyl)acetamide (3n). Compound 3n was prepared according to GP1 using 4-acetamidobenzenediazonium chloride (2n).…”
mentioning
confidence: 99%